Penegakan Hukum Terhadap Terhadap Tindak Pidana Pencurian Minyak Mentah Badan Operasi Bersama PT. Bumi Siak Pusako Kabupaten Siak Melalaui Pembocoran Pipa (illegal Tapping) - Bagas Aryo Seno Putra; Zulfikar Jayakusuma; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The crime of theft of crude oil from BOB PT. Bumi Siak Pusako, Siak Regency through pipe leakage is a series of criminal acts expanding from South Sumatra where the high level of this criminal activity. The criminal act of stealing crude oil through pipelines or called Illegal Tapping has resulted in a decrease in crude oil production for companies that experience this, of course, resulting in losses to the state and in this process also has a significant impact on environmental pollution. As we know that oil is a natural resource that cannot be renewed and one of the natural resources that supports the prosperity of the people.This research is classified as sociological legal research (empirical), because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in the jurisdiction of Siak Regency. The data sources used are primary data and secondary data. Data collection techniques in this study were interviews and literature review.The conclusions obtained from this study are, first, that law enforcement efforts against the criminal act of theft of crude oil from BOB PT. Bumi Siak Pusako, Siak district, through the pipe leakage is still not running well, which is necessary to give birth to a new legal product regarding this crime. Second, obstacles in the enforcement of criminal law are influenced by several factors, namely statutory factors, societal and cultural factors, and law enforcement factors. Third, there needs to be an increase in law enforcement efforts for the theft of crude oil from BOB PT. Bumi Siak Pusako, Siak district through leakage of pipes both preventive (prevention) and repressive (action)Key words: law enforcement, crime, theft, crude oil, pipes